Exploring ambivalence: A psychoanalytic analysis of emotional complexity in selected Amharic novels - Dawit Dibekulu; Tesfaye Dagnew; Tesfamaryam G/Meskel (PLoS ONE, 2025)
This study examines the representation of ambivalence in the Amharic literary canon, focusing specifically on the novels Yäqënat Zār (Zar of Jealousy) and Emba ɨnna Saq (Tears and Laughter). While previous research has explored various themes within Amharic literature, there is a notable gap in the exploration of ambivalence as a central emotional and psychological force in these narratives. This research seeks to address this gap by analyzing the multifaceted expressions of ambivalence and its consequences within the selected novels. Through a psychoanalytic lens, it delves into how personal loss, cultural anxieties, and the complexities of identity intersect to shape the characters’ experiences. The study’s use of a qualitative approach within an interpretive paradigm is significant because it allows for an in-depth exploration of the meanings and implications embedded in the text. Close reading, as the primary method, enables a detailed analysis of the text’s language, structure, and themes, helping to uncover layers of meaning that extend beyond surface-level understanding. The descriptive and analytical research designs work together to identify key features of the text and analyze how these elements interact to convey deeper insights into cultural, historical, and social contexts. Ultimately, this approach is essential for interpreting how literature reflects human experiences and societal values. Close textual analysis reveals how ambivalence manifests in the characters’ internal conflicts, regrets, and anxieties, shedding light on the complexities of their psyches. The findings highlight ambivalence as a driving force that reflects the tensions between cultural expectations, societal pressures, and individual desires. This research underscores the importance of ambivalence in Amharic literature, offering a richer understanding of the emotional and psychological depth within these narratives. The study also suggests that further exploration of ambivalence in other genres of Amharic literature is warranted, taking into consideration the unique cultural and national contexts that shape these emotional experiences.